Identification of risk factors for recurrent febrile convulsion - Nadirah Rasyid Ridha; P. Nara; Hadia Angriani; Dasril Daud (Indonesian Pediatric Society, 2009)
Background Febrile convulsion (FC) occurs in about 2 to 4percent of all children, approximately one third of whom willthen develop recurrent febrile convulsion (RFC). Risk factorsfor RFC are family history of convulsions, an age of less than 18months, a relatively lower temperature and shorter duration offever preceeding the first FC.Objective The aim of the study was to determine the risk factorsfor RFC.Methods One hundred children aged 6 months to 5 years withFC or RFC were included in this case-controlled study, which wascarried out from July 2006 to June 2007. Data on the children'sfirst FC were collected from medical records and the family historywas taken directly from the parents.Results Fifty children with RFC and 50 children withoutrecurrence were included in this study. An age of less than 18months (P< 0.0001, COR= 71.37), a family history of FC(P< 0.0001, COR= 6.00), and a fever duration ofless than 12hours preceding the first FC (P< 0.0001, COR = 4.96) wereassociated with a risk of recurrence. A relatively lower degree oftemperature at first febrile convulsion did not increase the riskfor RFC (P = 1.21). Multivariate logistic regression showed thatyounger age and shorter duration of fever preceding the first FCwere associated with RFC.Conclusion Younger age and shorter duration of fever precedingthe first FC are associated with an increased risk ofRFC.